Criteria of Shari`ah supervisory board: a comparative study between guidelines of Bangladesh Bank and Bank Negara Malaysia - Amanullah, Muhammad (2014)
An important factor that makes Islamic banking and finance different from conventional banking and finance is that the Islamic one follows the rules of Islamic Shari`ah, while the conventional one does not do so. In order for Islamic banking and finance to be certain that they are following the Shari`ah rulings, they must have a Shari`ah supervisory board. An important duty of this board is to determine that the products, services, policies and guidelines and all other activities of an Islamic bank are in compliance with the Shari`ah rulings. To perform their duty properly, the members of this board should possess certain criteria. Bangladesh Bank has spelled out some guidelines for these criteria briefly. Likewise, Bank Negara Malaysia also has provided some guidelines. Following analytical, comparative and critical methods the main objectives of this research paper are to highlight the guidelines of these two banks on these criteria, compare them and evaluate them in light of Shari`ah guidelines on these criteria spelled out by contemporary Muslim jurists. This paper is divided into following sections: introduction, criteria of the members of Shari`ah supervisory board according to contemporary Muslim jurists, evaluation of the guidelines of Bangladesh Bank on these criteria, evaluation of the guidelines of Bank Negara Malaysia on these criteria, comparison between the guidelines of Bangladesh Bank on these criteria and that of Bank Negara Malaysia.